The effect of strength and speed on the effectiveness of performing some basic skills among junior handball players under 15 years old. A field study on the Boussaada youth handball team. - Houiche, zakaria (sports creativity, 2025)
The researcher addressed the impact of certain physical fitness components on the effectiveness of basic handball skills among young players. The study aimed to identify the effect of both muscular strength, specifically speed-strength and explosive power, on the performance of jump shots (shooting a medicine ball to the farthest distance) and passing skills. It also sought to determine the impact of speed on shooting, feinting, and passing skills in handball among players under 15 years of age. The study was conducted on the under-15 youth team of Boussaâda amateurs, consisting of 12 players. To achieve this objective, physical and skill tests were administered, adapted from scientific literature and validated by experts. Due to the nature of the topic, a descriptive correlational approach was employed. Statistical methods included the arithmetic mean, standard deviation, and Pearson's simple correlation coefficient. The conclusion was that there is a significant correlation between the physical fitness components and the handball skills under study.